2015
DOI: 10.1371/journal.pone.0146073
|View full text |Cite
|
Sign up to set email alerts
|

Bay 61-3606 Sensitizes TRAIL-Induced Apoptosis by Downregulating Mcl-1 in Breast Cancer Cells

Abstract: Breast cancer cells generally develop resistance to TNF-Related Apoptosis-Inducing Ligand (TRAIL) and, therefore, assistance from sensitizers is required. In our study, we have demonstrated that Spleen tyrosine kinase (Syk) inhibitor Bay 61–3606 was identified as a TRAIL sensitizer. Amplification of TRAIL-induced apoptosis by Bay 61–3606 was accompanied by the strong activation of Bak, caspases, and DNA fragmentation. In mechanism of action, Bay 61–3606 sensitized cells to TRAIL via two mechanisms regulating m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Therefore, Syk could become a new therapeutic target in some cancer cell types. For example, a recent study indicated that a Syk inhibitor could sensitise TRAIL-induced apoptosis by downregulating Mcl-1 in breast cancer cells [38]. In this study, we strengthened our previous speculations that Syk is an upstream signalling molecule for EGFR in SCC cell lines and mediates EGF-induced IL-8 gene expression.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, Syk could become a new therapeutic target in some cancer cell types. For example, a recent study indicated that a Syk inhibitor could sensitise TRAIL-induced apoptosis by downregulating Mcl-1 in breast cancer cells [38]. In this study, we strengthened our previous speculations that Syk is an upstream signalling molecule for EGFR in SCC cell lines and mediates EGF-induced IL-8 gene expression.…”
Section: Discussionsupporting
confidence: 87%
“…The genome of PVY encodes two polyproteins, a larger polyprotein of about 3000 amino acids and a shorter one translated from a 2 + frameshift in the P3 coding region. These polyproteins are cleaved by viral proteases, subsequently generating eleven mature proteins (Kim et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although TRAIL exhibits promising specificity for cancer cells over normal cells, the effectiveness of anti‐cancer therapy using TRAIL has remained ambiguous because of the resistance of primary tumors to TRAIL . Multiple studies have been performed to address these limitations using sensitizers, and sensitizing mechanisms involving apoptosis‐associated proteins, such as Mcl‐1 and IAP; TRAIL receptors; and various other signaling molecules that control cancer cell processes, such as autophagy and metabolism, have been exploited . Among these, TRAIL receptor induction was previously shown to trigger TRAIL sensitization and ligand‐independent apoptosis, and the resulting putative TRAIL receptor sensitizer may be applicable for treating other refractory cancers.…”
Section: Discussionmentioning
confidence: 99%